Going Beyond Mathematics Anxiety in Primary and Middle School Students: The Role of Ego‐Resiliency in Mathematics. Issue 3 (22nd June 2020) - Donolato, Enrica; Toffalini, Enrico; Giofrè, David; Caviola, Sara; Mammarella, Irene C.
ABSTRACT: Previous research examined the influence of math anxiety (MA) on performance in mathematics, but few studies compared the contribution of MA to other forms of anxiety, such as test and general anxiety (GA). Unlike MA, ego‐resiliency promotes the management of challenges, and has been positively associated with mathematics performance. In this study, we investigated the specific influence of MA, test‐ and GA, and ego‐resiliency on mathematics performance after controlling for intelligence. Children from grades 5 to 8 ( N = 274) were assessed with self‐report tools measuring MA, test and GA, and ego‐resiliency, and completed intelligence and mathematical tasks. The results of structural equation models showed that MA had a main negative effect on mathematics performance, over and above the effect of test‐ and GA. Ego‐resiliency had a positive effect on mathematics performance, and was negatively associated with GA. Our findings are discussed in terms of the implications for intervention programs to reduce anxiety and sustain ego‐resiliency.